Integration of civilization elements in dance choreography: A study of traditional Malaysian dances - Taim, Mohd Asnari; Amat, Asmiaty; Mohd Tamring, Budi Anto (Imaji: Jurnal Seni dan Pendidikan Seni, 2025)
This paper examines the approach of integrating elements of civilization such as history, customs, and social systems in the choreography of traditional Malaysian dances and how these elements reflect the identity and cultural values of various ethnic groups. This study uses a qualitative approach through field observations, interviews with artists and cultural experts, as well as the analysis of visual documentation from dance performances. Data were analyzed thematically to identify cultural patterns contained in dance movements, choreography arrangements, costumes, and the social context of the performances. The research results show that elements of civilization such as Hindu-Buddhist influence, Islamization, and colonialism have shaped the structure and symbolism in dance, while customs and social norms set ethical boundaries and gender roles in performances. Traditional dance also serves as a medium of social communication, cultural education, and a symbol of community unity. The evolution of choreography is also detected through adaptation to the influences of globalization and technology, which pose challenges for the preservation of cultural identity. However, responsible innovation allows for the continuity of traditional dance in a contemporary context. Overall, the integration of civilizational elements in choreography not only strengthens the value of cultural heritage but also makes dance a dynamic reflection of Malaysia's multicultural.Keywords: Traditional dance, civilization, choreography, culture, heritage